Effects of Climatic Conditions on Agricultural Output in Kaduna State - Yusuf Usman, Aminu; Muktar, Iliyasu (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Variability in climatic conditions entails large instability, resulting from natural and man-made factors such as drought, flooding, erosion, carbon emissions, deforestation and so on. Agriculture is highly dependent on weather patterns in developing countries. Changes in environmental variables are thus, likely to have impact on agriculture more than other sectors of the economy. This paper attempts to examine the effects of climatic conditions on agricultural output with reference to Kaduna State, Nigeria. The study adopted the Autoregressive Distributed Lag (ARDL) model as its empirical framework. It collected secondary data on four (4) climatic conditions, namely, average maximum temperature, average amount of rainfall, and average relative humidity, and on the average crop yield from various sources, including the Nigerian Meteorological Agency and Kaduna Agricultural Development Agency (KADA), Kaduna State office. The result of the findings suggests that there is no long-run relationship between average crop yield and climatic conditions. Whereas, it revealed a non-linear relation between climatic conditions and average crop yield in the state, it found the effects of climatic conditions on agricultural output to be far-reaching on farmers' income and food security. It however, recommended the adoption of irrigation farming (on a full-scale) so as to cushion the overall impact of inadequate rainfall in that part of the country amongst others